Study of the hormonal and reproductive factors associated with low back pain in reproductive female - Singh, Neetu; Kumar, Dileep; Singh, Jigyasa; Singh, Santosh Kumar; Chandanan, Ani; Gupta, Radhika (International Journal of Research in Medical Sciences, 2017)
Background: Low back pain related disability and work absence accounts for high economical costs in modern society. A prevalence of 28-80% has been found with increase of prevalence with age and female preponderance. Methods: The present study was conducted on 250 non pregnant women complaining of low back pain attending department at Upper India Sugar Exchange Maternity Hospital, Department of Obstetrics and Gynaecology, GSVM Medical College, Kanpur during the period of one year. A brief questionnaire was used to screen, among the respondents, the occurrence of low back pain in the past year. Results: Low back pain was associated with high BMI, high waist circumference, more number of children, irregular and prolonged duration of menstruation, young maternal age at first birth and with history of abortion. Conclusions: Hormonal and reproductive factors are associated with low back pain.